Sarcomatous Component in Uterine Carcinosarcomas Correlates With Advanced Stage and Poorer Prognosis. (January 2018) - Podoll, Mirna B.; Moghadamfalahi, Mana; Faber, Erin; Bishop, Julie Anne; Alatassi, Houda
Abstract : Uterine carcinosarcomas, also known as malignant-mixed mullerian tumors, are rare and highly aggressive tumors whose prognostic factors remain controversial. The stage at the time of presentation is the most important prognostic factor thus far, but little information exists on the prognostic impact of the sarcomatous component (SC) in these tumors. We reviewed 21 cases of uterine carcinosarcomas and estimated the volume of the SC in each case. This information was correlated with the stage of the tumor at presentation. The percentage of the SC was also used to stratify the patients into 2 cohorts (high percentage of SC and low percentage of SC), and the 2 patient cohorts were compared based on the available follow-up data to identify prognostic differences. Patients with a lower concentration of SC (<30%) typically presented with low stage of disease when compared with their counterparts. Although not statistically significant ( P =0.1966), our data suggest a correlation between a lower concentration of SC with longer follow-up and longer survival rates when compared with those of patients presenting with higher volumes of the SC (≥30%). Greater volume of the SC is seen in advanced stage tumors, which could serve as an indicator of prognosis.